Effect of Obesity on Prone Percutaneous Nephrolithotomy Outcomes: A Systemic Review - Ozgor, Faruk; Ucpinar, Burak; Binbay, Murat (Urology Journal, 2016)
Purpose: With decreased physical activity, growing sedentary lifestyle, and high fat diet, obesity has become a pandemic disease all over the world. In this review, we aim to assess the effect of obesity on prone percutaneous nephrolithotomy.(PNL) outcomes. Materials and Methods: We performed a comprehensive review of the published articles in PubMed®, Medline, Scopus, Cochrane database from January 1, 2004 through June 31, 2015, using the key words; body mass index, obesity, morbid obesity, super obese, urolithiasis, nephrolithiasis, percutaneous nephrolithotomy and percutaneous lithotripsy. Original research articles published in English language with accessibility to the full text article were analyzed for our review. Results: At the end of the evaluation, we found 12 articles in English language, analyzing the effect of obesity on prone PNL outcomes. Except one study, eleven studies were evaluated in this review had a retrospective nature without randomization. Stone free status of patients was in a wide range between 49%-90% in obese patients and 41%-90% in morbid obese patients. Conclusion: PNL is a safe and effective treatment modality for renal stone(s) in obese and morbid obese patients. However, effect of body mass index on PNL outcomes including operation time, fluoroscopy screening time, hospitalization time, complications and stone free status are still debatable.